What can the bacterial community of atta sexdens (Linnaeus, 1758) tell us about the habitats in which this ant species evolves? - Ramalho, Manuela de Oliveira [UNESP]; Martins, Cintia; Morini, Maria Santina Castro; Bueno, Odair Correa [UNESP] (MDPI, 2020)
Studies of bacterial communities can reveal the evolutionary significance of symbiotic interactions between hosts and their associated bacteria, as well as identify environmental factors that may influence host biology. Atta sexdens is an ant species native to Brazil that can act as an agricultural pest due to its intense behavior of cutting plants. Despite being extensively studied, certain aspects of the general biology of this species remain unclear, such as the evolutionary implications of the symbiotic relationships it forms with bacteria. Using high-throughput amplicon sequencing of 16S rRNA genes, we compared for the first time the bacterial community of A. sexdens (whole ant workers) populations according to the habitat (natural versus agricultural) and geographical location. Our results revealed that the bacterial community associated with A. sexdens is mainly influenced by the geographical location, and secondarily by the differences in habitat. Also, the bacterial community associated with citrus differed significantly from the other communities due to the presence of Tsukamurella. In conclusion, our study suggests that environmental shifts may influence the bacterial diversity found in A. sexdens.
Keywords: Bacterial diversity; Conservation; Environment; Extensive cultivation; Sustainable development